2018
DOI: 10.1007/s00128-017-2227-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Experimental Lead Exposure on Testis of the Chestnut Capped Blackbird Chrysomus ruficapillus

Abstract: Lead (Pb) effects on testis histology, as well as sperm quality and oxidative status were evaluated in male Chestnut Capped Blackbird (Chrysomus ruficapillus). Wild blackbirds were captured, immediately sampled (field group) or kept in captivity and treated with a single intraperitoneal injection of saline solution (control) or saline solution with Pb acetate (50 or 100 mg/kg Pb). Seven days after injection, whole blood, ductus deferens and testis samples were collected. Increased Pb concentrations were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Even though Pb is slowly eliminated from the body, prolonged exposure can harm numerous organs, including the testicles [31]. Studies have revealed that Pb exposure can result in impaired function of the testicles and semen quality in male animals because the testes are particularly susceptible to Pb toxicity [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Even though Pb is slowly eliminated from the body, prolonged exposure can harm numerous organs, including the testicles [31]. Studies have revealed that Pb exposure can result in impaired function of the testicles and semen quality in male animals because the testes are particularly susceptible to Pb toxicity [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Yet there has been a long-term interest in sperm motion characteristics of passerine birds, because faster sperm are presumed to outcompete rival sperms in the "race" to the ovum and more ejaculated motile sperm are likely to increase the odds of sperm from a certain male fertilizing the ovum. In addition, some passerine sperm motility parameters can also be used as indicators of the impact of pollutants in a wide range of species (Møller et al 2008(Møller et al , 2014Leidens et al 2018).…”
Section: Introductionmentioning
confidence: 99%